1999
DOI: 10.1523/jneurosci.19-06-01998.1999
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stabilization of Muscle Nicotinic Acetylcholine Receptor by Rapsyn

Abstract: Although the metabolic half-life of muscle endplate acetylcholine receptor (AChR) changes during development and after denervation in the adult, little is known about the molecular mechanisms that influence receptor stability. We have investigated the effect on AChR turnover of its interaction with rapsyn, a 43 kDa peripheral membrane protein that is closely associated with the AChR in muscle cells and is required for its clustering at endplates. Both in transfected COS cells and in cultured myotubes from raps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…The β subunit has been chemically cross-linked to rapsyn in Torpedo membranes (33), and the association with rapsyn metabolically stabilizes the receptor by reducing its turnover at the EP (34). Our results show that the deletion mutations in the β subunit reduce cell surface more than total cellular expression, indicating that this region of the subunit may contribute to receptor turnover as well as to subunit oligomerization.…”
Section: Discussionmentioning
confidence: 76%
“…The β subunit has been chemically cross-linked to rapsyn in Torpedo membranes (33), and the association with rapsyn metabolically stabilizes the receptor by reducing its turnover at the EP (34). Our results show that the deletion mutations in the β subunit reduce cell surface more than total cellular expression, indicating that this region of the subunit may contribute to receptor turnover as well as to subunit oligomerization.…”
Section: Discussionmentioning
confidence: 76%
“…There is a wealth of studies showing a direct correlation between the amount of rapsyn present at NMJs and the abundance or the metabolic stability of synaptic AChRs (Brockhausen et al, 2008;Gervasio et al, 2007;Gervasio and Phillips, 2005;Luo et al, 2008;Martinez-Martinez et al, 2009;Wang et al, 1999). Furthermore, mutations in the RAPSN gene are amongst the most frequent causes for myasthenic syndromes, which are characterised by activity-dependent muscle weakness (Beeson et al, 2008;Müller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is thought to slow the metabolic degradation of the AChR (46,47) and function downstream of the Agrin/MuSK signaling, leading to AChR clustering (48). Recently, we found that Rapsyn stabilizes AChR clusters by interacting with calpain, a calcium-dependent protease involved in ACh-induced dispersion of AChR clusters (8).…”
Section: Discussionmentioning
confidence: 99%